From theory to practice: lessons from transformative learning through a net-zero design competition - Mehmood, A.; Cheema, Abdur Rehman; Salam, M.; Ahmed, S. U. D.; Moghayedi, A.; Vassilev, V.; Aburamadan, R. (Informa UK Limited, 2025)
This practical note explores the impact of transformative learning through an international design competition focused on net-zero housing in South Asia, the Middle East and North Africa, and sub-Saharan Africa. By fostering interdisciplinary collaboration and hands-on engagement, the competition equipped young professionals with practical skills to address climate-responsive housing challenges. Participants designed affordable, sustainable homes using renewable energy solutions tailored to middle-income households in a Global South setting, supported by workshops, skill-building sessions, and expert feedback. Survey findings highlighted the potential for such initiatives to bridge education, policy, and practice, promoting inclusivity and innovation. This work demonstrates the transformative role of experiential education in advancing sustainability considerations, addressing affordability, and aligning with the Sustainable Development Goals (SDGs).